Harold Phillip Winkel interviewed by Gregg Borschmann in The people's forest oral history project - Winkel, Harold Phillip, 1946-; Borschmann, Gregg (Gregg John), 1955- (1996)
Harold Winkel, a logging contractor, axeman and third generation bushman speaks of his early years on the dairy farm at Mt Mee, north west of Brisbane; his family moving in the early 1950's to the upper Brisbane Valley to join his father who was felling the hoop pine; how his practical appreciation of the environment was taught to him at an early age by his father; how as a logging contractor he applied the flexible approach of a seasoned bushman to timber harvesting; by the 1980's that he could foresee the demise of the timber industry with the increasing public support for the environmental campaign against logging in forests; finally making the decision to get out of the timber industry after some thirty odd years.
Recorded on July 22 1996 in Dorrigo, N.S.W.
Digital master available
Timed summary and corrected transcript (typescript 55 leaves) available.
Keywords: Winkel, Harold Phillip, -- 1946- -- Interviews; Loggers -- Queensland -- Interviews; Loggers -- Queensland -- Economic conditions -- 20th century; Loggers -- Queensland -- Social conditions -- 20th century; Forest conservation -- Australia; Loggers; Wood choppers